Interaction Between Blood Vasculatures and Lymphatic Vasculatures During Inflammation - Wang SS; Zhu XX; Wu XY; Zhang WW; Ding YD; Jin SW; Zhang PH (Dove Medical Press, 2023)
Shun-Shun Wang,1,2,* Xin-Xu Zhu,1,2,* Xin-Yi Wu,1,2,* Wen-Wu Zhang,1,2 Yang-Dong Ding,1,2 Sheng-Wei Jin,1,2 Pu-Hong Zhang1,2 1Department of Anesthesia and Critical Care, The Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University, Zhejiang, People's Republic of China; 2Key Laboratory of Anesthesiology of Zhejiang Province, The Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University, Zhejiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Sheng-Wei Jin; Pu-Hong Zhang, Department of Anesthesia and Critical Care, The Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University, 109 Xueyuan Road, Wenzhou, Zhejiang Province, 325027, People's Republic of China, Email jinshengwei69@163.com; drzhangpuhong@wmu.edu.cnAbstract: Physiological activity cannot be regulated without the blood and lymphatic vasculatures, which play complementary roles in maintaining the body's homeostasis and immune responses. Inflammation is the body's initial response to pathological injury and is responsible for protecting the body, removing damaged tissues, and restoring and maintaining homeostasis in the body. A growing number of researches have shown that blood and lymphatic vessels play an essential role in a variety of inflammatory diseases. In the inflammatory state, the permeability of blood vessels and lymphatic vessels is altered, and angiogenesis and lymphangiogenesis subsequently occur. The blood vascular and lymphatic vascular systems interact to determine the development or resolution of inflammation. In this review, we discuss the changes that occur in the blood vascular and lymphatic vascular systems of several organs during inflammation, describe the different scenarios of angiogenesis and lymphangiogenesis at different sites of inflammation, and demonstrate the prospect of targeting the blood vasculature and lymphatic vasculature systems to limit the development of inflammation and promote the resolution of inflammation in inflammatory diseases.Keywords: inflammation, blood vessels, lymphatic vessels, lymphangiogenesis, angiogenesis